Industrialised Building System (IBS) Plan of Work - Mohd Reeza Yusof; Muhamad Faiz Musa; Noor Sahidah Samsudin; Mohammad Fadhil Mohammad; Mohd Nurfaisal Baharuddin (International Review of Management and Marketing, 2016)
Industrialised Building Systems (IBS) is a term used to describe construction method that produced building components manufactured in a factory, transported and assembled into a structure using appropriate machinery and equipment with minimal workers on site. The project life cycle is a project independent series of activities that commences from the starting point until the moment it was successfully delivered. Generally in a construction project, the phases or stages are initiating, planning, executing, monitoring and controlling as well as the closing stage. This paper is part of an on-going research on the Industrialised Building System (IBS) project management life cycle through the IBS approach in the Malaysian construction industry. The data and information presented is the review of the available relevant literature on this research topic. This paper incorporates an analysis of the definitions and IBS/Off-Site plan of work or similar to it outside Malaysia. The identification of the plan/cycle from the analysis is critically essential to becoming the fundamental foundation for further research into the subject matter. It is hoped that at the end of the core research, industry players will be provided with a guideline that adopts a concept of “cradle to grave” in managing IBS throughout its plan of work/ life cycle.